ANALISIS PENERAPAN PSAK NO. 45 TENTANG PELAPORAN KEUANGAN ORGANISASI NIRLABA PADA UTD KABUPATEN PEKALONGAN - Ariyanti, Rizka; Soraya, Laely T (JURNAL LITBANG KOTA PEKALONGAN, 2020)
Financial reporting as a decision-making aid must be recognized by all parties from all aspects, both forprofit organizations and non-profit organizations. The purpose of financial reports is to provide relevant information to meet the interests of organizational members, creditors and other parties who provide resources to non-profit organizations. This study aims to describe the preparation of the financial statements of the PMI Pekalongan Regency Blood Transfusion Unit as a non-profit organization with reference to PSAK No. 45. The location of this study is UTD PMI Regency, with research subjects Staff of the Finance and Administration Sub Division of Blood Transfusion Unit of PMI Pekalongan Regency.Data collection techniques used are through observation, documentation and interviews. The data analysis method used in this research is descriptive qualitative, by comparing theory and practice in the preparation of organizational financial reports. The results showed that overall, UTD PMI Pekalongan Regency has referred to the provisions of PSAK No. 45 regarding the financial reporting of non-profit organizations, but there is 1 indicator in the financial statements of UTD PMI Pekalongan Regency that is not in accordance with PSAK No. 45, namely the classification of liabilities that have not been grouped into short-term and long-term liabilities. Keywords: Application of PSAK No. 45, Financial Reporting, Nonprofits,